Penelitian Analisis Beban Kerja Karyawan Di Badan Pengelola Tabungan Perumahan Rakyat (BP Tapera) Dengan Metode Work Load Analysis - Karya Bakti Kaban (PT Pustaka Cendekia Group, 2024)
A leader and former chairman and CEO of Xerox Corporation, Anne M. Mulcahy said: Employees who believe that management cares about them as whole people, not just as employees, will be more productive, more satisfied, and more fulfilled. Words that we may have heard often but are sometimes less meaningful to leaders in the company. The results of management attention have a major impact on the final results of employee performance / productivity. The implementation of an efficient and effective organization is a requirement in the era of globalization which is full of competition and limitations in all fields, this reality demands professionalism of employee resources / apparatus in carrying out organizational affairs, however, what is happening now is that the professionalism expected from apparatus resources has not been fully realized. One of the main causes is because there is a mismatch between employee competence and the position they occupy and the mismatch is caused by the composition of employee expertise or skills that are not yet proportional, likewise the distribution of employees still does not refer to the real needs of the organization, in the sense that it is not based on the workload of the organization. The implementation of workload analysis is essentially expected to fulfill the demands of the need to create effectiveness and efficiency as well as adequate professionalism of human resources of the apparatus in each agency and be able to carry out general government and development tasks smoothly based on the spirit of devotion to the community, nation and state. In addition, the implementation of workload analysis can produce a benchmark for employees / organizational units in the division of tasks and carrying out their activities, namely in the form of norms for work completion time, work efficiency levels, and workload and work performance standards, compiling employee formations, and improving work procedure systems and other management. The results of the workload analysis can also be used as a benchmark for: (1) Seeing the level of employee workload whether the conditions are appropriate (fit), excessive (over load), and even or lacking (under load) which ultimately increases work productivity and other steps in order to improve coaching, improvement and utilization of state apparatus both in terms of institutions, administration and personnel. (1) Determining and planning the number of employees (work force planning) for the organization in the future. One thing that may be faced by the Company's management is how to link and match employee productivity with the Company's productivity. It is often experienced that employee productivity is not in line with the Company's productivity, when the Company seems to have not achieved or is still far from the targets set at the beginning of the year while employee productivity results are considered to be productive. Productivity itself is the ability of a person or group of people to produce goods and services within a certain time that has been determined or according to plan, while labor productivity refers to the output that can be produced by a worker, this applies to a company, industry, or economy. In a business, employee work productivity is directly related to company performance, where high employee work productivity will help the company to continue to make a profit and compete with its competitors. Workload analysis that produces Full Time Equivalent (FTE) or the level of employee workload compared to their working hours. This will produce whether employees in their work with the existing daily time (workload) are appropriate, lacking or even overloaded. If the employee's workload is still not fulfilled or under load, of course we can assume that the employee is not yet productive. In this study, an analysis was conducted on the workload in the form of FTE from employees to see the workload of each employee. The final results of this study were obtained: (1) Of the 185 employees, there were 59 employees (32%) in the UNDERLOAD category, 83 employees (45%) who were NORMAL/FIT, and there were 34 employees (18%) who were in the OVERLOAD category, then there were 9 (5%) employees whose FTE had not been measured, because of the new work period. (1) There were 34 employees (18%) who were OVERLOAD so that it needs to be a concern in the future